The Comparison of the Regula-Falsi Method and the Ridder Method in Determining Non Linear Equation Roots - Melrosa, Feby (UNIVERSITAS NEGERI PADANG, 2023)
As the development of technology, there are many problems in mathematics that required a structured solutions, one of which is finding a solution to a non-linear equation called a root equation. This solution can be solved numerically when an analytical solution is difficult to find. Numerical methods that can be used to find roots of nonlinear equations include the Regula-Falsi method and the Ridder method. The purpose of this research is compare the results in the form of root value comparison, the number of iterations and the error rate from the Regula Falsi method and the Ridder method. Based on the research findings, it can be concluded that the root values obtained from the Regula Falsi method and the Ridder method are the same. However, for some equations, the Ridder method is preferable and constantly gets fewer iterations compared to the Regula Falsi method.